From Words to Wounds: Translating Narrative Violence and Ideology in Laut Bercerita (The Sea Speaks His Name) - Cahyadi, Ni Made Dewi; Kholifah, Asrofin Nur; Handoyo, Raden Pujo (Makassar State University, 2025)
Abstract. Translating literary works into various languages is a common practice to expand wider audience. In literary works, violence often serves as an instigating element that might unsettle readers, making it a critical challenge for translators to convey while maintaining the nuances of the original text. The novel Laut Bercerita by Leila S. Chudori is one such literary work that best illustrates narrative violence. It depicts the struggle of activists against the authoritarian government during the New Order era. Investigating how narrative violence is re-expressed is essential, as certain forms of violence may not be acceptable in the target language, which highlights the importance of understanding to what extent a translator faithfully transfers such content from the source language to the target one. This study accordingly examines the types of narrative violence based on Slavoj Žižek theory of violence and digs into the translation strategies used by the translator in transferring the narrative violence using Almjirab’s concept of translation strategies. The research then identifies the translator’s ideology in revoicing narrative violence through Venuti’s concepts of foreignization and domestication. Employing a qualitative descriptive approach, the researcher conducts an in-depth analysis to reveal the proposed problems. The findings unveil three types of violence: subjective violence (84%), systemic violence (14%), and symbolic violence (2%). Moreover, four translation strategies were found: substitution (63%), censorship or omission (20%), taboo for taboo (11%), and euphemism (6%). The study concludes that the translator predominantly employed a domestication ideology, adopting a target language-oriented approach to ensure readability, linguistic acceptance, and emotional resonance. These findings show that domestication enhance the text’s accessibility for the target audience while potentially diminishing the source text’s linguistic and cultural elements. Keywords: translation studies; translation strategies; ideology of translation; taboo words; narrative violence